Two insular regions are differentially involved in behavioral variant FTD and nonfluent/agrammatic variant PPA. (January 2016) - Mandelli, Maria Luisa; Vitali, Paolo; Santos, Miguel; Henry, Maya; Gola, Kelly; Rosenberg, Lynne; Dronkers, Nina; Miller, Bruce; Seeley, William W.; Gorno-Tempini, Maria Luisa
Abstract: The non-fluent/agrammatic variant of primary progressive aphasia (nfvPPA) and the behavioral variant frontotemporal dementia (bvFTD) are focal neurodegenerative disorders belonging to the FTD-spectrum clinical syndromes. NfvPPA is characterized by effortful speech and/or agrammatism and left frontal atrophy, while bvFTD is characterized by social–emotional dysfunction often accompanied by right-lateralized frontal damage. Despite their contrasting clinical presentations, both disorders show prominent left anterior insula atrophy. We investigated differential patterns of insular sub-region atrophy in nfvPPA and bvFTD. Based on knowledge of insular connectivity and physiology, we hypothesized that the left superior precentral region of the dorsal anterior insula (SPGI) would be more atrophic in nvfPPA due to its critical role in motor speech, whereas the ventral anterior region would be more atrophied in bvFTD reflecting its known role in social–emotional–autonomic functions. Early stage nfvPPA and bvFTD patients matched for disease severity, age, gender and education and healthy controls participated in the study. Detailed clinical history, neurological examination, neuropsychological screening evaluation, and high-resolution T1-weighted brain magnetic resonance imaging (MRI) were collected. Voxel-based morphometry (VBM) was applied to perform group comparisons across the whole brain and in bilateral insula region of interest (ROI). Correlation analyses between insular sub-region atrophy and relevant clinical features were performed. Whole brain group comparisons between nfvPPA and bvFTD showed the expected predominantly left or right anterior insular atrophy pattern. ROI analysis of bilateral insula showed that the left SPGI was significantly more atrophied in nfvPPA compared to bvFTD, while the bilateral ventral anterior and right dorsal anterior insula sub-regions were more atrophied in bvFTD than nfvPPA. Only left SPGI volume correlated with speech production abilities, while left and right ventral anterior insula volumes correlated with ratings of aberrant eating behavior. These two FTD clinical variants show different patterns of insular sub-region atrophy in the left precentral dorsal anterior and bilateral ventral anterior regions, providing further evidence for the role of these sub-regions in speech production and social–emotional function.